Pharmacotherapy of cancer pain with opioid analgesics - Krtinić Dane A.; Gvozdenović Ljiljana V.; Vicković Sanja V.; Lučić-Prokin Aleksandra L.; Knežević Aleksandar L.; Milijašević Dragana S.; Nedin-Ranković Gorana G.; Živadinović Biljana S.; Zdravković Ranko M.; Todorović-Mitić Mirjana M.; Stojanov Aleksandar D.; Jovanović Hristina M.; et al. (Srpsko lekarsko drustvo, 2023)
Introduction: Selection of analgesics should be based on the World Health Organization (WHO) analgesic ladder, beginning with non-opioid analgesics in combination with adjuvants for mild pain, weak opioids with adjuvants are indicated for moderate pain, while potent opioids, non-opioids and adjuvants are recommended for severe pain. Methods: The facts presented in this paper are expanded by searching for recent literature data in the following index-data-bases: SCI index, PubMed, Google Scholar, Scopus, and by using adequate key words. The idea supporting this paper was to make practice easier for clinicians who are engaged in supportive oncology and to help in adequate and up-to-date malignant pain management in oncology patients in everyday practice. Topic: Initial opioid dose should be low, and long-acting opioid dose should be gradually increased and titrated considering daily requirements of short-acting opioid formulation due to pain breakthrough. It is mandatory for patients on long-acting opioid treatment to be provided with fast-acting medication for breakthrough pain treatment. The following long-acting strong opioids formulations are available in Serbia - oxycodone, oxycodone/ naloxone fixed combination, hydromorphone, tapentadol, fentanyl. A patient and his/her family should be warned about possible side effects of opioids, primarily morphine. There is great fear of prescribing opioid analgesics due to their possible side-effect of tory depression. Opiophobia is defined as exaggerated concern about the consequences of medical use of opioids. The risk of opioids is estimated to overweight the benefits of the treatment, resulting in the fact that they are not used where indicated. Avoiding opioid prescriptions is one of the biggest barriers for successful treatment of cancer pain. Conclusion: Oncology patients with moderate and severe pain have a constitutional right not to tolerate pain and they have a right to strong opioid treatment. Implementation of analgesic elevator is recommended. There should not be any fear of addiction or other side-effects that can be controlled, and the benefits greatly outweigh the risks of possible side-effects in these patients. Cancer pain management should be an equally important element of overall cancer treatment. Only by multimodal and multidisciplinary treatment approach satisfactory analgesic effects may be achieved while minimizing adverse side-effects.